2010
DOI: 10.1007/s00586-010-1433-7
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical factors of importance for outcome after lumbar disc herniation surgery: long-term follow-up

Abstract: Factors as age, sex, smoking, duration of leg pain, working status, type/level of disc herniation and psychosocial factors have been demonstrated to be of importance for short-term results after lumbar discectomy. There are few studies with long-term follow-up. In this prospective study of lumbar disc herniation patients undergoing surgery, the result was evaluated at 2 and 5-10 (mean 7.3) years after surgery. Predictive factors for satisfaction with treatment and objective outcome were investigated. Out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 27 publications
1
76
3
2
Order By: Relevance
“…The surgical method used in this study, microdiscectomy, seems to be the preferred method in many publications [13][14][15][16][17], and has fewer complications than other methods [18]. This study shows that 75% of the patients with limb paresis due to herniated lumbar disc had full recovery 12 months after micro discectomy.…”
Section: Discussionmentioning
confidence: 67%
“…The surgical method used in this study, microdiscectomy, seems to be the preferred method in many publications [13][14][15][16][17], and has fewer complications than other methods [18]. This study shows that 75% of the patients with limb paresis due to herniated lumbar disc had full recovery 12 months after micro discectomy.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, a prospective Swedish study found that 89% of patients who underwent lumbar discectomy were working in some capacity 2 years after surgery. 13 The factors predictive of return to work at 2 years included a shorter duration of leg pain (less than 6 months) and less time spent on sick leave preoperatively (less than 2 months).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recurrence was defined as appearance of symptoms of LDH, confirmed by MRI at the same site and level or another level and re-operation was defined for re-surgery for recurrence or any other complication related with index surgery.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] All of these studies, based upon western population, have found three important variables; medical insurances, worker's compensation and sick leave as important predictors of outcome after LDH surgery. 7,8 But these predictors are not present among Nepalese population because of different social, economic and cultural factors. Hence, it can be assumed that predictors for outcome after LDH surgery will be different in Nepalese population.…”
Section: Introductionmentioning
confidence: 99%